Failure to detect anti-idiotypic antibodies in the autoimmune response to IA-2 in Type 1 diabetes. (30th July 2013) - Richardson, Carolyn C.; McLaughlin, Kerry A.; Brown, Thomas J.; Morgan, Diana; Feltbower, Richard; Powell, Michael; Furmaniak, Jadwiga; Rees Smith, Bernard; Christie, Michael R.
Abstract: The concept that immune responses to self antigens are regulated by anti-idiotypic networks has attracted renewed interest following reports of circulating factors within IgG fractions of serum that impair detection of autoantibodies with autoantigen. Thus, preclearance of sera with bead-immobilised monoclonal autoantibodies to the Type 1 diabetes autoantigen GAD65, or prebinding of serum antibodies to protein A Sepharose prior to addition of antigen, increases immunoreactivity detected in serum samples consistent with the trapping on the beads of anti-idiotypic antibodies that block antibody binding to the autoantigen. The aim of this study was to investigate the presence of anti-idiotypic antibodies to another major target of autoantibodies in Type 1 diabetes, IA-2. As previously observed for GAD65, preadsorption of serum samples with immobilised monoclonal IA-2 autoantibody, or prebinding to protein A Sepharose, resulted in substantial increases in subsequent immunoprecipitation of radiolabeled IA-2 in a proportion of samples. However, control experiments indicated that the increases seen on pre-incubation with immobilized autoantibodies were caused by displacement of the antibody by serum IgG, whereas impaired detection of immunoreactivity in liquid-phase radiobinding assays was the result of formation of insoluble complexes that bind poorly to protein A. The results emphasise the importance of direct demonstration of specific binding of antibodies to the idiotype in the study of idiotypic networks in autoimmunity. Variability between patients in formation of insoluble immune complexes has implications for the design and standardization of autoantibody assays for diabetes prediction.